2011
DOI: 10.1016/j.jmb.2011.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Impact of Cancer-Related Missense Somatic Mutations

Abstract: A number of large scale cancer somatic genome sequencing projects are now identifying genetic alterations in cancers. Evaluation of the effects of these mutations is essential for understanding their contribution to tumorigenesis. We have used SNPs3D, a software suite originally developed for analyzing non-synonymous germ line variants, to identify single base mutations with a high impact on protein structure and function. Two machine learning methods are used, one identifying mutations that destabilize protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 61 publications
(143 reference statements)
2
43
0
Order By: Relevance
“…An increasing number of studies use the predicted impact in a variety of applications, and have reported that SNV impact predictions match experimental findings 130,132,133. Such applications include guiding mutagenesis,134,135 identifying disease associated genes in both Mendelian and common diseases,1,136139 separating disease-causing variants from linkage disequilibrium variants,140 identifying somatic mutations that drive cancer,65,141,142 and predicting the overall phenotype of an organism 143. These applications highlight the value of SNV impact prediction and the need for further improvement.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies use the predicted impact in a variety of applications, and have reported that SNV impact predictions match experimental findings 130,132,133. Such applications include guiding mutagenesis,134,135 identifying disease associated genes in both Mendelian and common diseases,1,136139 separating disease-causing variants from linkage disequilibrium variants,140 identifying somatic mutations that drive cancer,65,141,142 and predicting the overall phenotype of an organism 143. These applications highlight the value of SNV impact prediction and the need for further improvement.…”
Section: Applicationsmentioning
confidence: 99%
“…The MutationAssessor method predicted the impact of over 10,000 nsSNVs from the COSMIC database,175 which combined with the total number of mutations in a gene and the frequency of each mutation in different tumors, ranked genes for cancer association, recovering known drivers (TP53, PTEN, etc) and suggesting many others 65. The SNPs3D method, consisting of two SVMs based on protein stability and homology respectively, was applied to about 2000 somatic mutations from colorectal and breast cancer to find that virtually all mutations in known cancer genes are predicted to impact protein function and therefore can be detected by nsSNV impact prediction methods 142. These methods produced intriguing novel predictions and may foreshadow wider use of nsSNV impact predictions to elucidate cancer mechanisms.…”
Section: Applicationsmentioning
confidence: 99%
“…A few methods make use of protein structure to directly identify high impact variants that affect protein stability, for example SNPs3D structure [26]. Use of this method to study monogenic disease [26] and cancer [27] found the majority of mutations to result in a change in protein thermodynamic stability, implying a role in folding or half-life. One of the most popular methods, Polyphen2 [18] makes use of a combination of profile and structure information.…”
Section: Introductionmentioning
confidence: 99%
“…Missense mutations, usually somatic, also play a major role in cancer [30], and application of the computational methods provides evidence that these also often have a high impact on protein function [27,31]. The role of high impact missense variants in common, complex trait, disease is less well established.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the close relationship between protein structures and their function altered by cancer-related missense mutations [96,97]. Vuong et al presented a protein pocket-based computational pipeline to study the functional consequences of somatic mutations in cancer [67].…”
Section: Structural Genomics-based Approachmentioning
confidence: 99%